The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.2172/5649933
|View full text |Cite
|
Sign up to set email alerts
|

Initial TMX-U thermal-barrier experiments

Abstract: Tab is in Informal report intended primarily for Intern*! or limited external dtaribatloo. Tbe ophkm mi coudiuiom slated ore those of Ike author and nuy or may not be Oust or the Laboratory. Work performed under (be auspices of the U*S> Dcpartraeat of Energy by the I-avrenoe LlTermore Laboratory under Contract W-740S-£ng-48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…Slow FRC formation may be possible by using neutral beams. This FRM approach came close to success a decade ago [15], and later studies [14, 63-65, 174, 172] suggest that it may be worth further consideration. High energy particles from neutral beams could help to achieve stable FRCs with large values of s by maintaining strong kinetic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slow FRC formation may be possible by using neutral beams. This FRM approach came close to success a decade ago [15], and later studies [14, 63-65, 174, 172] suggest that it may be worth further consideration. High energy particles from neutral beams could help to achieve stable FRCs with large values of s by maintaining strong kinetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2XIIB experiments sketched in Fig. 12, off-axis neutral beams drove ion currents in a mirror-confined plasma target in order to form and sustain an FRM [15]. Field reversal was probably not achieved, for reasons that remain unclear.…”
Section: Slow Frc Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed explanation of the operation of this machine is outside the scope of the present discussion and is presented elsewhere [3,4]. For reference, a schematic of the magnetic field profile is shown in Fig.…”
Section: Particle Source Measurements With Video Datamentioning
confidence: 99%
“…In the area of nuclear fusion, it has been proposed that the electrostatic potential is created along a magnetic field line positively to improve the confinement of plasmas along magnetic field lines in an open-ended magnetic confinement device, [1][2][3][4][5] which is called a ''tandem mirror.'' The subsequent experimental efforts at demonstrating the electrostatic potential formation along a magnetic field line have revealed that the electrostatic potential in the end-mirror cells in a tandem mirror is created by a different mechanism from the theoretical concept.…”
Section: Introductionmentioning
confidence: 99%